Punicic Acid a Conjugated Linolenic Acid Inhibits TNFα-Induced Neutrophil Hyperactivation and Protects from Experimental Colon Inflammation in Rats - Boussetta, Tarek; Raad, Houssam; Lettéron, Philippe; Gougerot-Pocidalo, Marie-Anne; Marie, Jean-Claude; Driss, Fathi; El-Benna, Jamel (PLOS ONE, 2009)
Background Neutrophils play a major role in inflammation by releasing large amounts of ROS produced by NADPH-oxidase and myeloperoxidase (MPO). The proinflammatory cytokine TNFα primes ROS production through phosphorylation of the NADPH-oxidase subunit p47phox on Ser345. Conventional anti-inflammatory therapies remain partially successful and may have side effects. Therefore, regulation of neutrophil activation by natural dietary components represents an alternative therapeutic strategy in inflammatory diseases such as inflammatory bowel diseases. The aim of this study was to assess the effect of punicic acid, a conjugated linolenic fatty acid from pomegranate seed oil on TNFα-induced neutrophil hyperactivation in vitro and on colon inflammation in vivo. Methodology and Principal Findings We analyzed the effect of punicic acid on TNFα-induced neutrophil upregulation of ROS production in vitro and on TNBS-induced rat colon inflammation. Results show that punicic acid inhibited TNFα-induced priming of ROS production in vitro while preserving formyl-methionyl-leucyl-phenylalanine (fMLP)-induced response. This effect was mediated by the inhibition of Ser345-p47phox phosphorylation and upstream kinase p38MAPK. Punicic acid also inhibited fMLP- and TNFα+fMLP-induced MPO extracellular release from neutrophils. In vivo experiments showed that punicic acid and pomegranate seed oil intake decreased neutrophil-activation and ROS/MPO-mediated tissue damage as measured by F2-isoprostane release and protected rats from TNBS-induced colon inflammation. Conclusions/Significance These data show that punicic acid exerts a potent anti-inflammatory effect through inhibition of TNFα-induced priming of NADPH oxidase by targeting the p38MAPKinase/Ser345-p47phox-axis and MPO release. This natural dietary compound may provide a novel alternative therapeutic strategy in inflammatory diseases such as inflammatory bowel diseases.